Sustainable Development of Promotional Strategies to Increase the New Students at Yapekdi Private Junior High School Dolok Ilir Dolok Batu Nanggar District, Simalungun Regency - Susilo, Hariadi; Salliyanti; Silalahi, Amlys Sahputra (Talenta Publisher, 2022)
The community service activity program for the Universitas Sumatera Utara Team, based on the results of an initial survey at the Yapekdi Middle School, the problem was that there was a lack of students registering as new students in 2021/2022, the promotion strategy carried out by the school had not yet influenced the community to register their children and the condition of some classrooms that were damaged so it was feared that it would have a bad effect on students who were studying inside. Solutions for 2022/23 Promoting sustainable development and providing one year scholarships to 20 students, promotional strategies to attract public interest by distributing flyers, installing banners, and renovating classrooms. Therefore, the school has accepted 20 students for the 2022/2023 school year. Then the outcomes achieved, Mass Media Publications and activity videos. Next plan. Summit Proceedings with ISSN.